A subordinate position of a woman as a wife in the story “Haraç” (tax) by the Turkish writer Füruzan - Botalić, Melinda; Mulahmetović, Amela (Historical Thought, 2025)
As there are differences between male and female understandings and perceptions of the world, their experiences are not identical either. The authority of the father / husband or pater familias (as existed in ancient Rome) is the ultimate given in patriarchy, and as such - is inviolable. The primary goal of this paper is to show how the traditional family treats a woman, and how learned patterns of behavior determine a woman’s destiny. In the light of this, the traditionally and socially given practices by which, in the “ sacred “ institution of marriage, a woman is treated, and by which, as a total opposite, a man is percieved, have led to unequal power relations, which we tried to prove in this paper.